Affective Dysregulation Precedes Emergence of Psychosis-Like Experiences in a Community Sample of Young Adults. (22nd February 2022) - Bornheimer, Lindsay A; Martz, Meghan E; Suzuki, Takakuni; Tso, Ivy F; Burton, Cynthia Z; Li Verdugo, Juliann; Grove, Tyler; Heitzeg, Mary M; Taylor, Stephan F
Abstract: Affective dysregulation (AD) among persons with schizophrenia spectrum disorders, involving the tendency to exhibit sensitivity to minor stress and negative affective states, is an important diagnostic feature and relates to poorer functional and clinical outcomes. Studies of persons with elevated risk for psychosis demonstrate similar AD to those with schizophrenia, and literature suggest a potential influence of AD in the transition from psychosis-like symptoms (PLEs) to disorder. Cross-sectional investigations to date have supported the link between AD and psychosis, and longitudinal studies have mostly yielded mixed findings without demonstration of potential causal relationships between AD and psychosis. This study examined the concurrent and predictive relationships between AD and PLE in a community sample of youth ( n = 630) with attention to distinct facets of AD as a latent construct, including low resiliency, low reactive control, and negative emotionality, using structural equation to estimate a longitudinal cross-lagged and autoregressive model across 3 study waves from 15 to 24 years of age. As hypothesized, AD in the mid-teen years predicted subsequent PLE 3 years later. In addition, we found that increasing PLE in the end of the teen years related to a subsequent increase in AD in the early 20s. A cross-sectional relationship between AD and PLE in the mid-teen years was also supported. Findings overall describe important relationships between AD and PLE that appear to vary with developmental stage, implicating various factors to inform approaches for identifying youth who may be at risk for subsequent PLE or other mental health conditions.